European Political Facts of the Twentieth Century
X, 481 p.
Keywords: This new edition of the well established European Political Facts provides a wide-ranging and comprehensive work of reference on Europe in the twentieth century. There are sections on heads of state and ministers, elections, political parties, constitutions, wars and treaties, among many others. The end result provides an invaluable compendium for students, academics, journalists and researchers. Recent events, from developments in the European Union to conflicts in the Balkans, receive full attention. This latest edition of a pioneering reference work first published twenty-five years ago is an indispensable acquisition for all those studying twentieth-century Europe.